2011
DOI: 10.3171/2010.6.jns10142
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression for elderly patients with trigeminal neuralgia: a prospective study and systematic review with meta-analysis

Abstract: Although patient selection remains important, the authors' experience and the results of this systematic review with meta-analysis suggest that the majority of elderly patients with TN can safely undergo MVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 37 publications
2
91
1
2
Order By: Relevance
“…However, the masticatory function and the mechanical (touch) perception were better preserved after MVD than BC. There is a lack of comparative studies that have analyzed the outcomes of different types of neurosurgery for iTN, and despite the fact that there are clear criteria for the selection of surgical modalities, 18,24,26 for a great number of patients this choice is made according to the available technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the masticatory function and the mechanical (touch) perception were better preserved after MVD than BC. There is a lack of comparative studies that have analyzed the outcomes of different types of neurosurgery for iTN, and despite the fact that there are clear criteria for the selection of surgical modalities, 18,24,26 for a great number of patients this choice is made according to the available technique.…”
Section: Discussionmentioning
confidence: 99%
“…4 One limitation of this study is the impossibility of age matching. Although MVD is a safe procedure for patients of any age, 26 due to more severe comorbidities in older populations the younger patients were more often referred to MVD. There are age characteristics associated with the masticatory system and sensorial thresholds that could have affected, at least in part, the results obtained by this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We then divided the population into an elderly cohort and nonelderly cohort. The age used to define the elderly population has varied across publications, 29 ranging from 60 to 75 years, and therefore, we used 2 different age cutoffs to distinguish our elderly population. The data were analyzed using an age cutoff of 65 years and then reanalyzed with an age cutoff of 75 years.…”
Section: Methodsmentioning
confidence: 99%
“…As the incidence of TN increases with age, 17 the safety of MVD in the elderly population represents an important clinical question for treating physicians. Several small studies, 2,8,9,12,13,25,27,30 including a recent prospective analysis, 29 have suggested that the efficacy and safety of MVD in elderly patients are comparable with those in younger patients. Unfortunately these studies are limited by small sample sizes.…”
mentioning
confidence: 99%